How and for how long is literacy taught in early childhood education? A multiple-case study of the classroom practices of seven teachers. Issue 5 (3rd September 2018) - Rodríguez, Inés; Clemente, Maria; Ramírez, Elena; Martin-Domínguez, Jorge
ABSTRACT: With a view to understanding and reflecting upon the form that initial literacy practices take, this paper seeks to analyse how seven teachers in early childhood education in Spain introduce the teaching of reading and writing. A multiple-case study has been conducted; the data were gathered by video-recording the sessions (a total of 105 hours). Two qualitative data analysis systems were applied, one for analysing the classroom practices that breaks the classes down into the main types of actions, with recurrent organisational patterns, and another categories system which permits the analysis of the tasks for the initial literacy teaching within the classroom practices. We have been able to identify the tasks, the types of activities that are held in all the classes, and the time each teacher spent on the initial teaching of literacy. The results are coherent with prior studies since teaching practices are mainly focused on teaching the written code. In all the analysed classroom sessions, teachers dedicate a big amount of time to the initial teaching on reading and writing. Finally, teachers create their own personal teaching dynamics, which means that over the literacy process we encounter a highly diverse range of practices across the different teachers.